Pelatihan Penentuan Harga Pokok Produksi Pada Kewirausahaan Pangan Non Beras BBPJN XVIII Papua, Wilayah 2 Kabupaten Merauke - Siti Rofingatun (UNIVERSITAS CENDERAWASIH, 2019)
This activity aims to provide training to the BBPJN Women's Dharma Group in Merauke Region 2 about Determining the Cost of Production in Every Non-Rice Food Entrepreneurship. This activity amounts to 30 people. By practicing and simulating to determine the cost of production of Non-rice Food Processed Products.